Transformation of Personnel Management in Improving Islamic Education - Solehan Solehan (International Journal of Educational Evaluation and Policy Analysis, 2024)
Changes in personnel management are crucial along with increasing demands for the professionalism and competence of teaching staff in Islamic educational institutions. This transformation covers various aspects, starting from recruitment and selection, competency development, to teacher performance evaluation. The research method used in this article is a literature study that analyzes various library sources related to personnel management and Islamic education. The research results show that implementing effective personnel management can increase teacher motivation and performance, which in turn has a positive impact on the quality of learning and student achievement. In addition, the integration of Islamic values ​​in the personnel management process can create a conducive and harmonious work environment, which greatly supports the achievement of Islamic education goals. This article concludes that personnel management transformation is a strategic step that must be taken by Islamic educational institutions to face the challenges and dynamics of the current world of education. . Daryanto, H. M. (2001). Administrasi pendidikan. Jakarta: Rineka Cipta. Depdikbud. (1994). Pedoman pelaksanaan kurikulum pendidikan dasar: Sekolah dasar. Jakarta: BP Dharma Bakti. Handoko, T. H. (2001). Manajemen dan sumber daya manusia. Yogyakarta: BPFE. Mulyasa, E. (2002). Manajemen berbasis sekolah. Bandung: Remaja Rosda Karya. Mulyasa, E. (2007). Manajemen berbasis sekolah: Konsep, strategi, implementasi. Bandung: Rosda Karya. Pidarta, M. (1997). Landasan kependidikan stimulus pendidikan bercorak Indonesia. Jakarta: PT Rineka Cipta. Pidarta, M. (2004). Manajemen pendidikan Indonesia. Jakarta: PT Asdi Mahasatya. Pidarta, Made. (2004). Manajemen Pendidikan Indonesia. Jakarta: PT. Asdi Mahasatya Samani, M. (2000). Revitalisasi sekolah menengah kejuruan. Jakarta: Pusat Penelitian Balitbang Depdiknas. Samani, Muchlas. (2000). Revitalisasi Sekolah Menengah Kejuruan. Jakarta: Pusat Penelitian Balitbang Depdiknas Ulfatin Nurul, Triwiyono Teguh, (2016). Manajemen Sumber Daya Manusia Bidang Pendidikan. Jakarta: Rajawali Pers Ulfatin, N., & Triwiyono, T. (2016). Manajemen sumber daya manusia bidang pendidikan. Jakarta: Rajawali Pers. Wilson, B. (2012). Manajemen sumber daya manusia. Jakarta: PT Gelora Aksara. Wilson, Bangun. (2012). Manajemen Sumber Daya Manusia. Jakarta: PT. Gelora Aksara